Diversificación morfológica de los primates platirrinos: una aproximación craneofuncional comparativa - Pérez, Sergio Iván (2017)
Evolutionary history of platyrrhines resulted in an outstanding morphological variation of their craniofacial structures. The early divergence of lineages and the occupation of varied niches are potential causes for this diversity. Our work aims to explore the patterns of morphological variation in the skull of platyrrhines of South America and to test the hypothesis that explains shape diversity as a function of size change. Here, skull lateral radiographs of 12 species of platyrrhines -each species represented a different genus- were analyzed using an approach that combines the craniofunctional theory and methodological tools from geometric morphometric. Results showed that morphological differentiation between genera can be only partially explained by their phylogenetic structure and there may be other ecological factors involved. Additionally, major cranial components presented a relatively independent variation between them, being the facial shape more influenced by the size than the neurocranium. In sum, craniofunctional theory and geometric morphometric gave some clues to formulate hypothesis about development and functional processes related to the origin and maintenance of macroevolutionary patterns of morphological diversity.